The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/mrd.23653
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated genes in undifferentiated spermatogonia and Sertoli cells are associated with the spermatogenic arrest in cattleyak

Abstract: Hybrid male sterility (HMS) is a reproductive isolation mechanism limiting the formation of fertile offspring through interspecific fertilization. Cattleyak is the interspecific hybrid presenting significant heterosis in several economic traits, but HMS restricted its wide reproduction in cettleyak breeding. In this study, we detected the specifically expressed genes of a variety of cells (undifferentiated spermatogonia, primary spermatocytes, secondary spermatocytes, haploid spermatids, sperm, Sertoli cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…All these results suggested that the Sertoli cells of the cattle-yak testis were defective. In our previous study, we successfully cultured Sertoli cells in vitro, and compared the proliferation characteristics and gene expression differences of functional and marker genes of yak and cattle-yak [8] . There has been no deep report about the transcriptome level of Sertoli cells in yak and cattle-yak.…”
Section: Introductionmentioning
confidence: 99%
“…All these results suggested that the Sertoli cells of the cattle-yak testis were defective. In our previous study, we successfully cultured Sertoli cells in vitro, and compared the proliferation characteristics and gene expression differences of functional and marker genes of yak and cattle-yak [8] . There has been no deep report about the transcriptome level of Sertoli cells in yak and cattle-yak.…”
Section: Introductionmentioning
confidence: 99%